Carrier lifetime and recombination in long-wavelength quantum-well lasers - Robinson, Gary Y., author; Thiagarajan, Prabhuram, author; Temkin, H., author; Menoni, Carmen S., author; Pikal, Jon M., author; IEEE, publisher (Colorado State University. Libraries, 1999)
We present a novel analysis for correcting the measured differential carrier lifetime to account for carrier population in both the barrier and separate confinement heterostructure (SCH) regions of quantum-well (QW) lasers. This analysis uses information obtained from the measured spontaneous emission spectra to correct the measured lifetime and obtain the intrinsic well lifetime. Once the intrinsic well lifetime is obtained, the intrinsic well recombination coefficients can also be obtained. We show that the carrier population in the barrier/SCH layers can significantly affect the measured carrier lifetime and the extracted recombination coefficients. We also show that this analysis yields transparency carrier density and differential gain numbers which are very different from those obtained with the traditional analysis and much closer to what is predicted for highly strained QW lasers. These differences indicate the importance of accounting for barrier/SCH carriers on the measurement of basic QW laser material properties.
Keywords: charge-carrier processes; electroluminescence; optical measurement; semiconductor lasers; quantum-well lasers